STUDENTS’ INSIGHT INTO ONLINE PLATFORM DURING THE COVID-19 PANDEMIC IN PUTRA SANG FAJAR BLITAR STATE COMMUNITY ACADEMY - Tambunan, Rika Wahyuni; Kurniawan, Hindra; br Tarigan, Fatin Nadifa (JAMI: Jurnal Ahli Muda Indonesia, 2022)
Objective: The purpose of this study was to identify the insight of Akademi Komunitas Negeri Putra Sang Fajar Blitar students regarding the use of online platforms as a substitute for face-to-face learning during the Covid-19 pandemic. This research departs from the impact caused by the spread of the Covid-19 pandemic, where all learning activities are carried out online. Materials and Methods. The method used in this research is qualitative. The data source is the result of a questionnaire via google form and conducted interviews with 5 selected students from each study program, of which a total of 20 students were analyzed in detail. The sampling technique used in this study was random sampling by distributing questionnaires via google forms and conducting interviews to explore students' perceptions of the use of social media in learning English. Results. The results of the research show that the use of online platforms in learning is very different from what students use in everyday life. It obtained that the zoom application is most often used as an alternative to online learning. Meanwhile, the WhatsApp application is often used by students in daily communication. Conclusion. The use of online platforms as learning alternatives provides several conveniences in the teaching and learning process in the pandemic era, such as time flexibility, interaction, and fun. However, it cannot be denied that the use of online platforms in learning also has obstacles, such as very monotonous learning, internet quota, difficulties in expressing creativity, poor responses, and uncertain schedules.